The pandemic between cyber fatwā-s and crisis management. The Islamic jurisprudence for minorities facing the Coronavirus (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
During the global pandemic, cyber fatwā-s play a key-role in guiding European Muslims’ religious and social conducts. Focusing on the ECFR jurisprudence, the paper unveils that the dramatic events were presented as the opportunity for a world-wide ethical and moral resurgence. A global pledge for social cohesion and change was advanced. Muslims were remembered to foster devotional aspects, to abide by Islamic provisions, and to support sick people and healthcare providers. Muslims were also urged to attentively conform to the official instructions issued by health authorities and State bodies. Specific attention was then paid to “fake news”: Muslims were recommended not to foster hearsay regarding vaccines and the Coronavirus. Since late 2020, the ECFR resumed its quasi ordinary activities; this indicates that the once new anti-pandemic norms have now been normalised.
Keywords: Pandemic; health crisis; muslim minorities; European Council for Fatwa and Research (ECFR); Ramadan